The HSP Immune Network in Cancer - Albakova, Zarema; Mangasarova, Yana (Frontiers in Immunology, 2021)
Heat shock proteins are molecular chaperones which support tumor development by regulating various cellular processes including unfolded protein response, mitochondrial bioenergetics, apoptosis, autophagy, necroptosis, lipid metabolism, angiogenesis, cancer cell stemness, epithelial-mesenchymal transition and tumor immunity. Apart from their intracellular activities, HSPs have also distinct extracellular functions. However, the role that HSP chaperones play in the regulation of immune responses inside and outside the cell is not yet clear. Herein, we explore the intracellular and extracellular immunologic functions of HSPs in cancer. A broader understanding of how HSPs modulate immune responses may provide critical insights for the development of effective immunotherapies.